The Half-stitched Amish Quilting Club - Brunstetter, Wanda E. (Uhrichsville, OH : Barbour Pub., Inc., 2012)
When Amish widow Emma Yoder offers quilting lessons, she acquires a diverse collection of six non-Amish students who form bonds with her and each other as they work through their problems and learn to create beautiful quilts.
Includes discussion questions.
Keywords: Amish -- Fiction; Quilting -- Fiction; Christian fiction